Large pyroelectric properties at reduced depolarization temperature in A-site nonstoichiometry composition of lead-free 0.94NaxBiyTiO3–0.06BazTiO3 ceramics - Balakt, Ahmed M.; Christopher, Shaw; Zhang, Qi (Springer, 2017)
Nonstoichiometry lead-free 0.94NaxBiyTiO3–0.06BazTiO3 (NxByT–0.06BzT) (from x = y = 0.5, z = 1.00 to x = 0.5, y = 0.534, z = 1.02) ceramic compositions were prepared by a conventional solid-state route. XRD shows that the compositions are at a morphotropic phase boundary where rhombohedral and tetragonal phases coexist. The depolarization temperature (Td) can be lowered by modifying x, y and z. The pyroelectric coefficient (p) of nonstoichiometry NxByT–0.06BzT compositions is greatly increased, compared with stoichiometry NBT–0.06BT composition, from 3.15 × 10−4 C m−2 °C−1 at room temperature (RT) and 23.9 × 10−4 C m−2 °C−1 at Td, and reaches maxima of 6.99 × 10−4 C m−2 °C−1 at RT and 75.3 × 10−4 C m−2 °C−1 at Td for x = y = 0.52 and z = 1. The figures of merits, Fi, Fv, and FD, also have been improved from 1.12 × 10−10 m v−1 and 0.021 m2 C−1 to 2.50 × 10−10 m v−1, 0.047 m2 C−1 and 16.63 × 10−6 Pa−1/2, respectively, for N0.52B0.52T–0.06BT composition at RT. Furthermore, N0.52B0.52T–0.06BT composition shows a huge enhancement in Fi, Fv and FD to 26.9 × 10−10 m v−1, 0.39 × 10−10 m2 C−1 and 138.7 × 10−6 Pa−1/2, respectively, at Td. The same composition also presents FC values which are ~2.58 and ~2.86 (×10−9 C cm−2 °C−1) at RT at 100 and 1000 (Hz). N0.5B0.534T–0.06BT and N0.5B0.534T–0.06B1.02T compositions show a large p values at a wide temperature range. The enhanced pyroelectric properties make nonstoichiometry N0.52B0.52T–0.06BT composition a promising candidate for pyroelectric and other applications at wide temperatures range.